Noelia López-Souto e Inés Velázquez-Puerto (eds.): VII Libros, imprenta y censura en la Europa meridional del siglo XV al XVII, Salamanca, IEMYRhd, 2020, 218 pp. - Baldacchino, Laura (Estudios Humanísticos. Filología, 2021)
Reseña